2022
DOI: 10.47144/phj.v55i3.2291
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Outcomes of Manual Thrombus Aspiration Versus Pre-Balloon Dilatation During Primary Pci for Total Occlusion

Abstract: Objectives: This study was designed to compare the in-hospital outcomes of primary PCI with export vs. primary PCI with the balloon in patients with total occlusion. Methodology: Consecutive patients with STEMI undergoing primary PCI with TA and pre-balloon dilatation were recruited in 1:1 ratio and post-procedure in-hospital mortality and complication rate (slow flow/no-reflow, contrast-induced nephropathy (CIN), and arrhythmias) were compared. Patients in the TA group were further stratified based on export … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…20 According to the research protocol, thrombus aspiration may have advantages and enhance primary outcomes in patients who had primary PCI and had TIMI 0 flow after a coronary wire had crossed the lesion. Similar to the findings of Kumar et al 19 the results of this investigation support thrombus aspiration over pre dilatation using a balloon catheter. In compared to the balloon pre dilatation arm, manual thrombus aspiration significantly reduced inhospital mortality and comorbidities such slow/no reflow, contrastinduced nephropathy, and arrhythmias.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…20 According to the research protocol, thrombus aspiration may have advantages and enhance primary outcomes in patients who had primary PCI and had TIMI 0 flow after a coronary wire had crossed the lesion. Similar to the findings of Kumar et al 19 the results of this investigation support thrombus aspiration over pre dilatation using a balloon catheter. In compared to the balloon pre dilatation arm, manual thrombus aspiration significantly reduced inhospital mortality and comorbidities such slow/no reflow, contrastinduced nephropathy, and arrhythmias.…”
Section: Discussionsupporting
confidence: 91%
“…This was in response to the publishing of unfavorable studies about the regular use of thrombus aspiration. 19 Although the study found no therapeutic advantage of regular thrombus aspiration in terms of improving objective clinical endpoints, some positive results were shown in subgroup analyses of patients with significant thrombus load. 20 According to the research protocol, thrombus aspiration may have advantages and enhance primary outcomes in patients who had primary PCI and had TIMI 0 flow after a coronary wire had crossed the lesion.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation